PERLINDUNGAN HUKUM TERHADAP HAK KONSUMEN ATAS INFORMASI PADA LABEL GAS LPG (STUDI PUTUSAN PENGADILAN NEGERI BOYOLALI NOMOR 2/PID.SUS/PN.BYL) - Winda Gadis Sukardi; Sri Bakti Yunari (Fakultas Hukum Universitas Tarumanagara, 2020)
Legal protection against consumers on the information on the gas labels of elpiji particulary the elpiji gas labels by CV. Berkat Ageng Suminar. Often in clean practice, elpiji gas on sale is not even on the menu in oplo, which has been a huge disservice to consumers on elpiji gas since the release of petroleum conversion policies into state-programmed elpiji gas. How does the legal protection against on the improper information of the gas labels elpiji, whether the court’s opinion No. 2/Pid.Sus/2017/PN.Byl related to consumer rights on information against the Consumer Protection Law No. 8 of 1999 . The research method used is normative juridical research by using secondary legal materials that are analyzed conclusively with a legal and case approach. Based on the analysis, legal protection of consumer in the Consumer Protection Law No. 8 of 1999 consists of compensation, compensation or restitution as stated in article 4 letter h, in addition to the right to seek advocacy in both courts and BPSK as a proper settlement effort as stated in article 4 letter e Consumer Protection Law No. 8 of 1999. Futher analysis of the content of district court ruling No. 2/Pid.Sus/2017/PN.Byl stands in conflict with article 8 letter a, b, and c that just about his endeavors can be convicted of criminal penalties and additional punishment of slave construction, judge judgments, payment of compensation, removal of employment. As a suggestion, more intensive coaching and surveillance of elpiji gas commercialized so that such cases would not happen again.